The Role of Exosomes in Viral Hepatitis and Its Associated Liver Diseases - Zhou, Hao; Yan, Zhi-han; Yuan, Yuan; Xing, Chen; Jiang, Nan (Frontiers in Medicine, 2021)
Exosomes, the important carriers between cells, can carry proteins, micro ribonucleic acids (miRNAs), long non-coding RNAs (lncRNAs) and other molecules to mediate cellular information transduction. They also play an important role in the pathogenesis, prognosis and treatment of viral hepatitis and its associated liver diseases. Several studies have reported that viral hepatitis and its associated liver diseases, including hepatitis A, B, C and E; hepatic fibrosis and hepatocellular carcinoma, were closely associated with exosomes. Exploring the role of exosomes in viral hepatitis and associated liver diseases will enhance our understanding of these diseases. Therefore, this review mainly summarised the role of exosomes in viral hepatitis and its associated liver diseases to identify new strategies for liver diseases in clinical practise.